Public procurement planning as an immunity to the budget process - V. V. Kikavets; Yu. K. Tsaregradskaya (Правоприменение)
The subject of the article is the research of public procurement in the context of budget expenditures efficiency.The purpose of the article is to confirm or disprove hypothesis that public procurement planning is the basis of a strategic relationship with the budget process. Their symbiosis can minimize any negative manifestations of a financial, economic and socio-political nature, including the consequences of crisis situations such as a pandemic.The methodology. The authors analyze many Russian and western scientific articles and monographs from the point of view of the budget process and planning of public procurement.The main results, scope of application. Planning of public procurement should be considered not as a separate need of one specific customer or a separate group of customers, but as a set of public consumption of all possible and necessary resources. The opposite approach will inevitably lead to additional budget costs for the elimination of consequences (natural, technological, etc.), associated, first of all, with the lack of a proper and clear understanding of the essence of planning public procurement and public demand for goods, works, services). Proper and carefully balanced procurement planning for all public needs not only ensures the immunity of the budget process for the current and subsequent periods, but also constitutes the basis for the prospective rational use of renewable and non-renewable resources, both internal (national) and external (foreign). This article has significant scientific and practical value. The study focuses on the key problem of public procurement in Russia-the lack of interaction between procurement planning and the budget process, pointing to the identified shortcomings of legal regulation that do not allow to quickly adapt to situational changes from outside. It is proposed to consider the introduction of strategic procurement planning for 5-10 years, which will not only determine the basis for financing public procurement from the budget, but also predict the revenues of the relevant budget, more accurately and correctly prioritize funding needs.The findings of the study allowed the authors to formulate proposals and recommendations. Consideration of the planning of public procurement, taking into account the budgetary process, will make it possible to develop recommendations in terms of adjusting certain norms of Law No. 44-FZ, which would allow the most efficient use of budget funds, both planned in advance and urgent purchases.Conclusions. A global crisis reveals the most pressing problems of governance of any state. The crisis obliges the government of any country to promptly analyze and rebuild the regulatory framework for effective financial, economic, social and political management. De-spite numerous reforms the budget process in the Russian Federation has retained significant bureaucratic costs that do not allow for rapid delivery of budget funds to each customer. The urgent need for rapid reallocation of budget funds for additional and priority purchases has shown the imperfection of the legal regulation of public procurement planning, which should be radically restructured. Since public procurement planning as an integral part of budget expenditure is not actually related to its revenues, such planning should be carried out based on the customer's needs for goods, works, and services for a longer period, which will allow a more meaningful and responsible approach to the issue of effective budget spending and overall resource consumption. Digital technologies in public procurement planning allow you to quickly compare all items of the plan with those planned and completed earlier in order to avoid duplication (unjustified repetition) of a similar purchase. Planning of budget purchases is not only an effective expenditure of budget funds, but also an efficient (lean) consumption of resources, including non-renewable ones.